Beyond breast cancer : a Mayo Clinic guide to healing and wellness - Haddad, Tufia C.; Ruddy, Kathryn J. (Mayo Clinic Press, 2023)
Beyond Breast Cancer: A Mayo Clinic Guide to Healing and Wellness is a supportive, practical guide to life after diagnosis and initial treatment for breast cancer. In this short, accessible book, Mayo Clinic breast cancer specialists Tufia C. Haddad, M.D., and Kathryn J. Ruddy, M.D., and colleagues offer their insights on how to navigate this new phase of the journey, including monitoring for signs of recurrence; optimizing diet, sleep and exercise habits; coping with lingering treatment effects; improving sexual health; managing money and insurance issues; and much more.